18S ribosomal RNA methyltransferase METTL5-mediated CDX2 translation regulates porcine early embryo development - Tengteng Xu; Mengya Zhang; Qiuchen Liu; Xin Wang; Pengfei Luo; Tong Liu; Yelian Yan; Naru Zhou; Yangyang Ma; Tong Yu; Yunsheng Li; Zubing Cao; et al. (Journal of Integrative Agriculture, 2025)
N6-methyladenosine (m6A) plays a key role in mammalian early embryonic development and cell lineage differentiation. However, the role and mechanisms of 18S ribosomal RNA (rRNA) m6A methyltransferase METTL5 in early embryonic development remain unclear. Here, we found that 18S rRNA m6A methyltransferase METTL5 plays an important role in porcine early embryonic development. METTL5 knockdown and overexpression significantly reduced the developmental efficiency of porcine early embryos and impaired cell lineage allocation. METTL5 knockdown apparently decreased the global translation efficiency in blastocyst, while METTL5 overexpression increased the global translation efficiency. Furthermore, METTL5 knockdown did not affect the abundance of CDX2 mRNA, but resulted in a significant reduction in CDX2 protein levels. Moreover, the low developmental efficiency and abnormal lineage distribution of METTL5 knockdown embryos could be rescued by CDX2 overexpression. Collectively, our results demonstrated that 18S rRNA methyltransferase METTL5 regulates porcine early embryonic development via modulating the translation of CDX2.